RADIATION THERMAL STRESSES IN MINERALS AND THEIR ROLE IN PROCESSES OF MAGNETITE QUARTZITE CONCENTRATION - Bochkarev G.P.; Vejgel't Yu.P.; Izotov A.S.; Rostovtsev V.I. (My University, 2001)
Dynamics of thermal stresses arising in minerals under action of accelerated electrons has been investigated. Results of the investigations have shown that the stresses determine technological indices of grinding and concentration. It has been noted that during processing the magnetite quartzites, variation of strength properties in radiation processing leads to increase in coefficient of the relative ore grinding. Content of iron in concentrates is increased by 0.6-1.3 percent. Increase in efficiency of concentration by 0.9-3.0 percent is observed. Losses of iron in tailings are simultaneously reduced by 0.4-1.3 percent.